IoT Based Forklift Worker Fatigue Monitoring Device - Mohd Arsad, Syira Syahira; Mazlan, Muhammad Hazli (Evolution in Electrical and Electronic Engineering, 2020)
Today we are becoming aware that most of the warehouse accidents occur due to fatigue or a drowsy forklift driver. In this study, a fatigue detection system to maintain the safety and health of the workplace was developed by monitoring the heartbeat and hand or finger grip force to detect forklift driver fatigue noninvasively and in real-time through an IoT application (Blynk) using a portable smart band. These alternative methods have been proposed to use with ESP32, Arduino Nano, pulse sensor, and force sensor which attached to the worker’s finger. If the driver is fatigued, then the system will give buzz and vibrate the alarm to alert the driver. The changes in the heartbeat rate and grip force were measured experimentally to ensure the accuracy and validity of measuring heartbeat rate and grip force. The experimental results prove that the developed system using pulse and force sensor is able to detect and monitor a person’s fatigue level.